Analysis of Multiculturalism Content in Book Édito 1 to Support Character Building of Beginner French Language Students - Eva Fitriyana; Sri Handayani (Hasanuddin University, 2026)
This study aims to analyze the multiculturalism content in the Édito 1 textbook and its contribution in supporting the strengthening of the character of beginning French language students. The study uses a qualitative approach with a content analysis method. The research data are in the form of text, images, and audio and video transcripts contained in the Édito 1 book. Data collection techniques are carried out through documentation, while data analysis is based on indicators of multiculturalism values which include learning to live in differences, building mutual trust, maintaining mutual understanding, upholding mutual respect, open-mindedness, appreciation and interdependence, and conflict resolution and non-violent reconciliation. The results of the study show that there are 48 multiculturalism contents spread across ten units, with the dominant indicators of learning to live in differences and appreciation and interdependence. These findings indicate that the Édito 1 book does not only function as a language learning tool, but also as a medium for instilling multicultural values that support the formation of student character, such as tolerance, openness, and appreciation of diversity. The absence of indicators for conflict resolution and reconciliation is understandable, as this book is intended for A1-level learners who are still at the basic communication stage. Therefore, Édito 1 is relevant as a teaching material to support multicultural education and strengthen the character of beginning French language students.